La escasa relevancia de la información contable sobre los activos intangibles en la valoración de las empresas innovadoras espa\~nolas: El caso de los sectores farmacéutico y biotecnológico - Gracia Rubio Martín; Mercedes Rodríguez Paredes; Juan Antonio Maroto Acín (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2013)
– This article analyzes the extent to which accounting standards adequately re ects the value of intangible assets as well as its usefulness for financial agents in the process of buying and selling companies. Based on a sample that includes price of private transactions and listed companies from the pharmaceutical and biotech Spanish sector in the period 2005-2011, we have analyzed: i) The performance of price-to-book ratio; and ii) Based on a regression model, the relevance of different accounting items in the price generation process, as well as what part of the intangible value of the company is not reflected in the financial statements. The authors conclude that traditional financial information must be complemented with an intellectual capital report.
Keywords: M41; C31; 330; intangible; value driver; fair value; intellectual capital report